A secular age beyond the west: forms of differentiation in and around the religious field (2014)
Based on an international research cluster of country specialists interested in the nexus between politics and religion in countries of Asia, Africa and the Middle East, we have edited, together with Shylashri Shankar, a volume that compares the place of religion and the secular in countries outside the West.1 All contributors took as their starting point Charles Taylor’s “A Secular Age” (2007), in which the author argues that the widespread availability of an option of not believing first evolved in the North Atlantic world. He examines the processes by which this option emerged, mostly by focusing his inquiry 2 on developments in philosophy and religion (specifically, Western Christianity), while social, economic, and political developments for a large part remain back stage. In the following, we summarize some of the lessons our contributors have drawn from their case studies, sometimes paralleling, often contrasting those developments Taylor found to be key in the emergence of a secular age in the West. We close with a sociological framework through which contestations around religion and state can be systematically schematized and compared.